2017
DOI: 10.2147/ott.s134599
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of cyclooxygenase-2 expression in patients with esophageal cancer: evidence from a meta-analysis

Abstract: Published studies have investigated the prognostic role of cyclooxygenase-2 (COX-2) expression in patients with esophageal cancer (EC), but the result remains controversial. Thus, this meta-analysis was conducted to comprehensively evaluate the impact of COX-2 expression on the prognostic value in patients with EC. Relevant studies were identified from PubMed, EMBASE, and Web of Science databases. Studies that detected the COX-2 expression by immunohistochemistry and evaluated the relationship between COX-2 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…26 Three of these studies found that high PTGS2 expression was associated with poorer overall survival, [16][17][18] consistent with a 2017 metaanalysis by Hu et al (pooled HR 2.13, 95% CI 1.62-2.79). 11 Of the two previous studies investigating cancer-specific survival, Prins et al found that, although PTGS2 expression was an independent predictor of poor overall survival, associations were nonsignificant in an analysis of cancer-specific survival after adjustment for confounders (HR 1.55, 95% CI 12 The differences in improved survival for patients with high PTGS2 expression tumours observed in this study contrast with previous evidence. This may be because all patients in our cohort underwent neoadjuvant chemotherapy, whereas previous studies all excluded patients who received any chemotherapy (Table 4).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…26 Three of these studies found that high PTGS2 expression was associated with poorer overall survival, [16][17][18] consistent with a 2017 metaanalysis by Hu et al (pooled HR 2.13, 95% CI 1.62-2.79). 11 Of the two previous studies investigating cancer-specific survival, Prins et al found that, although PTGS2 expression was an independent predictor of poor overall survival, associations were nonsignificant in an analysis of cancer-specific survival after adjustment for confounders (HR 1.55, 95% CI 12 The differences in improved survival for patients with high PTGS2 expression tumours observed in this study contrast with previous evidence. This may be because all patients in our cohort underwent neoadjuvant chemotherapy, whereas previous studies all excluded patients who received any chemotherapy (Table 4).…”
Section: Discussioncontrasting
confidence: 87%
“…Three of these studies found that high PTGS2 expression was associated with poorer overall survival, consistent with a 2017 meta‐analysis by Hu et al . (pooled HR 2.13, 95% CI 1.62–2.79) . Of the two previous studies investigating cancer‐specific survival, Prins et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, COX-2 overexpression is also observed in esophageal and gastric cancer (14,15). Elevation of COX-2 expression is also associated with a shorter survival time among patients with CRC and esophageal cancer (16,17). However, conflicting results have been reported in the association between COX-2 expression and survival in patients with GC (18).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the COX-2 peroxidase activity may contribute to production of mutagens ( Figure 1). [5][6][7][8] Enhanced COX-2 expression was demonstrated in various types of human malignancies: carcinomas of colon, 9,10 breast, 11,12 lung, 13,14 stomach, 15,16 esophagus, 17,18 pancreas, 19 bladder, 20 prostate, 21 ovary, 22,23 cervix, 24,25 osteosarcomas, 26,27 gliomas, 28,29 and Hodgkin lymphomas. 30 In most of the studies, it was shown that cancer progression is accompanied by an increase in COX-2 levels and may have prognostic potential.…”
Section: Cyclooxygenase-2 In Cancermentioning
confidence: 99%